Nannofossil distribution in the late Jurassic- Naokelekan and Barsarin Formations, Miran Oil field, well-2-, Kurdistan, Northeastern Iraq - Kharajiany, Soran O. A.; Mohialdeen, Ibrahim M. J. (Sulaimani Journal for Pure and Applied Sciences, 2018)
The Naokelekan and Barsarin Formations of the Upper Jurassic are studied in the oil well Miran -2- at the Sulaimani area of Kurdistan. The study is focused on the determination of nannofossil contents and age of both rock units. Based on the calcareous nannofossil marker species, twelve cutting samples were selected from both formations in that well. The lithology of the Naokelekan Formation is dominated by black shale, and some white rock fragments, while the lithology of the Barsarin Formation is characterized by high abundance of darkgrey and grey limestone towards bottom, where the ratio of milky- white limestone is increased upward. The nannofossil species that identified for the first time here are Conusphaera mexicana, Polycostella senaria, Nannoconus compressus, Helenea staurolithina, Watznaueria britannica, Watznaueria barnesiae, Lotharingius hauffii, Faviconus multicolumnatus and Parhabdolithus robustus. This assemblage proved the Late Jurassic; the index nannofossils and biostratigraphic zonation indicated that the age of the Naokelekan Formation is dated back to Early Tithonian, and the Barsarin Formation to late Early-Middle Tithonian. Preservation of the calcareous nannofossils in the well is bad to moderate. The calcite grains are re-crystallized and caused difficulty in the identification.
Keywords: Naokelekan; Barsarin; Jurassic; Calcareous nannofossils; Conusphaera mexicana; Watznaueria britannica; Nannoconus compressus; Polycostella senaria; Miran Oil Field